Intraday Optimization of Pumped Hydro Power Plants in the German Electricity Market - Braun, Sebastian; Hoffmann, Rainer (Energy procedia, 2016)
Historically, the optimal production of hydro power plants was determined once day ahead. Today, many regulatory requirements in the German electricity market make this process much more complex: Power plant operators are committed to report information on planned production and even on provision of balancing energy of each single generator to transmission system operators. As soon as a deviation in the schedule occurs, the information hast to be updated and reported again. These requirements lead to the point where optimization of pumped hydro power plants can no longer be done manually. In order to fulfil these requirements, EnBW has developed its own optimization model and established a system-based day ahead and intraday asset optimization process. The optimization problem is formulated as a mixed integer problem which determines the minimum operating cost subject to all technical constraints of a hydrothermal portfolio and covering load. As a post-optimization of this new intraday optimization system we set up an effective multistage looping optimization algorithm for daily pumped hydro power plants considering e. g. reservoir limits, quarter-hourly prices, grid charges and availabilities. A real world case study is presented and discussed.